High-temperature-resistant emulsion type pressure-sensitive adhesive, aluminum foil tape and preparation method thereof

By adding acrylic acid and/or methacrylic acid and internal crosslinking agent to the pressure-sensitive adhesive of the aluminum foil tape, and adding nanoceramic particles, the problem of existing high-temperature resistant aluminum foil tape falling off and peeling under high temperature environments is solved, achieving higher temperature resistance and a safer production process.

CN119709059APending Publication Date: 2025-03-28JIANGYIN MEIYUAN IND CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411737810.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing high-temperature resistant aluminum foil tape is easy to fall off and peel off in a high-temperature environment, and the toluene used in the preparation of the raw glue is harmful to human health. The production process requires complete protective measures, and there is room for further improvement in the high-temperature resistant technology effect.

Method used

The emulsion-type high-temperature pressure-sensitive glue prepared by pre-emulsification and polymerization of the raw glue is used. The raw glue consists of reactive emulsifiers, monomers, deionized water, internal crosslinking agents, surfactants, alkaline buffers and initiators. By adding acrylic acid and/or methacrylic acid and internal crosslinking agents, the glass transition temperature and crosslinking degree of the polymer are increased, and nanoceramic particles are added to the pressure-sensitive glue to improve temperature resistance.

Benefits of technology

The stability of pressure-sensitive adhesive in a high temperature environment above 140 degrees Celsius is achieved, the service life of aluminum foil tape is extended, and the temperature resistance and creep resistance of the tape are improved through the addition of nanoceramic particles, and the health risks of using toluene are avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a high-temperature-resistant emulsion type pressure-sensitive adhesive which comprises the following components in parts by weight: 5-8 parts of a reactive emulsifier, 300-365 parts of a monomer, 200-300 parts of deionized water, 0-5 parts of an inner cross-linking agent, 0.2-1 part of a surfactant, 1-5 parts of an alkaline buffering agent and 1-5 parts of an initiator. The monomer contains 5-10 parts of methacrylic acid and / or acrylic acid. The emulsion is prepared through pre-emulsification and a polymerization reaction, and in the polymerization reaction process, 1-5 parts of nano ceramic particles are added; the invention further discloses an aluminum foil adhesive tape prepared from the pressure-sensitive adhesive, the surface of the aluminum foil adhesive tape is coated with nano ceramic particles with the thickness of 5-10 microns through an adhesive, and then the surface of an aluminum foil is coated with the pressure-sensitive adhesive; by adding (methyl) acrylic acid and nano ceramic particles into a monomer and constructing the aluminum foil tape with an aluminum foil-nano ceramic particle-pressure-sensitive adhesive structure, the temperature resistance range of the aluminum foil tape is widened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a pressure-sensitive adhesive, in particular to a high-temperature resistant emulsion-type pressure-sensitive adhesive, an aluminum foil tape and a preparation method thereof. Background Art

[0002] Aluminum foil tape is a composite film made of one or more layers of metal foil bonded with a pressure-sensitive adhesive. This material has good moisture-proof, waterproof, oil-resistant properties, and also has the advantages of good viscosity, strong adhesion, and anti-aging. Aluminum foil tape is widely used in many fields, and is often used for seam pasting of various aluminum foil composite materials, sealing of insulation nail punctures, and repair of damaged parts. In addition, in places where electromagnetic shielding is required, such as inside electronic products such as monitors, laptops, and copiers, aluminum foil tape also plays an important role as a shielding material. High temperature environments often cause aluminum foil tape to fall off and peel off. For this reason, it is necessary to develop a high-temperature resistant pressure-sensitive adhesive for use in the production process of aluminum foil tape.

[0003] The invention patent with announcement number CN109679540A discloses a method for preparing a high-temperature resistant adhesive. The aluminum foil tape prepared by this method can withstand temperatures of up to 120°C, but toluene, which is seriously harmful to human health, is used in the preparation of the original glue, which requires more complete protective measures during the production process; secondly, the preparation method must be matured for one week after the aluminum foil is coated with the adhesive, which brings storage and production costs; thirdly, the technical effect of the high-temperature resistance of the aluminum foil tape can be further improved.

[0004] The invention patent application with announcement number CN117720681A discloses an emulsion, preparation process and application of a multi-component water-resistant tape. Its water resistance is improved by adding isooctyl acrylate to the monomer. Based on this formula, the high temperature resistance of the aluminum foil tape can be further improved, thereby expanding its application market. Summary of the invention

[0005] The main purpose of the present invention is to provide a green and safe high temperature resistant pressure sensitive adhesive which can withstand high temperature above 140 degrees Celsius without failure. The secondary purpose is to make the above pressure sensitive adhesive into an aluminum foil tape product.

[0006] To achieve the above object, the technical solution provided by the present invention is as follows: an emulsion-type high temperature resistant pressure sensitive adhesive prepared by pre-emulsification and polymerization of raw rubber:

[0007] The original rubber composition includes:

[0008] 5-8 parts of reactive emulsifier, 300-365 parts of monomer, 200-300 parts of deionized water, 0-5 parts of internal crosslinking agent, 0.2-1 parts of surfactant, 1-5 parts of alkaline buffer, 1-5 parts of initiator;

[0009] The monomer comprises the following components: 85-105 parts of isooctyl acrylate, 190-220 parts of n-butyl acrylate, 20-30 parts of vinyl acetate, and 5-10 parts of methacrylic acid and / or acrylic acid.

[0010] Furthermore, the reactive emulsifier includes at least one of allyl ether sulfonate and acrylamide sulfonate.

[0011] Furthermore, the internal crosslinking agent includes N-hydroxymethylacrylamide and / or N,N'-methylenebisacrylamide.

[0012] Furthermore, the surfactant includes at least one of n-dodecyl mercaptan, n-hexadecyl mercaptan, sodium dodecyl sulfate, and sodium dodecylbenzene sulfonate.

[0013] Furthermore, the alkaline buffer includes sodium bicarbonate and / or potassium dihydrogen phosphate.

[0014] Furthermore, the initiator includes at least one of ammonium persulfate, benzoyl peroxide, and azobisisobutyronitrile.

[0015] The preparation method of the pressure sensitive adhesive is as follows:

[0016] Pre-emulsification:

[0017] S001: Mix the weighed reactive emulsifier evenly in half of the deionized water, which is called solution A; mix the monomer, internal crosslinking agent and surfactant evenly, which is called solution B;

[0018] S002: Add solution B dropwise into solution A, and the addition time is controlled to be completed within 1.5 to 2.5 hours;

[0019] It should be noted that, while the weight portion is enlarged, the dropping time can be controlled by increasing the number of dropping devices and (proportionally) increasing the amount of material added in a single drop, but in order to avoid spontaneous polymerization of the substrate leading to uneven mixing and preparation failure, the dropping time should be kept within the above range.

[0020] S003: Continue stirring the solution after the monomer has been added for 0.5 to 1.5 hours;

[0021] The pre-emulsification is completed, and the mixed solution that has completed the pre-emulsification step is called solution C;

[0022] Polymerization reaction:

[0023] S101: Add the buffer, initiator, remaining deionized water and 1-5 parts (by weight) of nano-ceramic particles into a reactor, turn on the stirring device of the reactor, stir at a speed of 100-300 rpm, heat the reactor to 75-85° C., maintain the temperature change within 5° C., and drip solution C into the reactor, and control the dripping time to be completed within 4-6 hours;

[0024] S102: After the dropwise addition is completed, the temperature of the reactor is raised to 90-95° C. and maintained for 2-3 hours;

[0025] S103: Turn off the heating device of the reactor, wait for the reactor to cool naturally to below 40° C., and then take out the product.

[0026] The polymerization reaction is completed, and the product that has completed the polymerization reaction step is called latex rubber.

[0027] Synthesis of pressure sensitive adhesive:

[0028] S201: 95-105 parts of the original latex, 20-30 parts of the thickening latex, 0.1-0.5 parts of the thickener, 0.5-1 parts of ammonia water, and 0.1-0.5 parts of the curing agent are added to a rubber mixing kettle, and stirred evenly in the rubber mixing kettle;

[0029] S202: Using a viscosity meter to measure the viscosity of the contents in the adhesive preparation kettle, when it is between 2000 and 3500 centipoise and the solid content is between 54 and 56%, it is a pressure-sensitive adhesive.

[0030] Further, the tackifying emulsion may be at least one of rosin tackifying emulsion, acrylic emulsion, styrene-butadiene emulsion (SBR), ethylene-vinyl acetate copolymer emulsion (EVA), and silicone emulsion, wherein preferably at least one of rosin tackifying emulsion (Snowtack 881G) and silicone emulsion.

[0031] Furthermore, the thickener may be at least one of an alkali swellable thickener, a cellulose thickener, and a polyacrylic acid thickener, wherein the alkali swellable thickener (JZ-290) is preferred.

[0032] Furthermore, the curing agent may be a water-based isocyanate curing agent.

[0033] The method for making aluminum foil tape includes:

[0034] S301: coating the pressure-sensitive adhesive on the aluminum foil through a coating machine, drying it in an oven at 110° C. to 120° C. for 2 to 4 hours to remove volatiles, and stopping drying when the solid content reaches more than 85%;

[0035] S302: Compounding the pressure-sensitive adhesive from which volatiles have been removed with a single-sided release paper to form a mother roll tape;

[0036] S303: Cutting the mother roll tape into small rolls of tapes of various specifications, thus completing the production of the aluminum foil tape.

[0037] Furthermore, before coating the aluminum foil in S301, the surface of the aluminum foil to be coated is firstly coated with an adhesive to form nano-ceramic particles with a thickness of 5 to 10 μm.

[0038] Furthermore, the adhesive is newly made polyvinyl formal.

[0039] Furthermore, the nano ceramic particles may be SiC, Si 3 N 4、 Al 2 O 3 , ZrO.

[0040] Furthermore, the method of brushing the nano-ceramic particles on the surface of the aluminum foil with an adhesive refers to adding a certain amount of nano-ceramic particles into the adhesive to form a suspension, stirring the suspension evenly, and then brushing the suspension onto the surface of the aluminum foil with a coating machine.

[0041] Furthermore, when two nano-ceramic particles are applied together in the present invention, the two nano-ceramic particles are mixed in a mass ratio of 1:1. Preferably, the mixing ratio of the nano-ceramic particles to the adhesive is 0.5-0.7 g / mL.

[0042] Furthermore, the particle size of the nano-ceramic particles is preferably 50 to 150 nm, and the thickness of the adhesive is 8 to 12 μm.

[0043] The advantages and beneficial effects of the present invention are:

[0044] 1. Acrylic acid and / or methacrylic acid are added to the monomer to increase the glass transition temperature of the polymer, thereby improving the temperature resistance;

[0045] 2. Internal crosslinking agents are added to the pressure-sensitive adhesive formula to increase the degree of crosslinking of the polymer, thereby improving its temperature resistance;

[0046] 3. Nano-ceramic particles are added during the preparation of the pressure-sensitive adhesive. These nano-ceramic particles can effectively transfer heat in the finished aluminum foil tape, reduce the internal temperature of the tape, and thus improve the temperature resistance of the aluminum foil tape;

[0047] 4. Nano-ceramic particles are bonded between the aluminum foil tape and the pressure-sensitive adhesive, so that when the aluminum foil tape is heated, the temperature can be quickly concentrated on one side of the aluminum foil, and the heat is quickly dissipated through the surface of the aluminum foil, thereby extending the service life of the pressure-sensitive adhesive. DETAILED DESCRIPTION

[0048] The invention discloses the composition and preparation method of a high temperature resistant emulsion pressure sensitive adhesive, and manufactures an aluminum foil tape based on the pressure sensitive adhesive, and makes further improvements on the structure of the aluminum foil tape to achieve the purpose of high temperature resistance.

[0049] The addition of methacrylic acid and / or acrylic acid and an internal crosslinking agent to the monomers of pressure-sensitive collagen adhesive is intended to improve the properties of the polymer such as the glass transition temperature to improve the temperature resistance of the pressure-sensitive adhesive. The mechanism of this process mainly involves the following aspects. Methacrylic acid and acrylic acid are hard monomers, and their addition can improve the cohesion of the pressure-sensitive adhesive. Cohesion refers to the mutual attraction between polymer molecular chains. Higher cohesion means that the molecular chains are more tightly bound, which helps to improve the temperature resistance of the pressure-sensitive adhesive and enable it to maintain good adhesion and structural stability at higher temperatures. The addition of methacrylic acid and acrylic acid can increase the Tg of the polymer, which means that the polymer can still maintain its glassy properties at higher temperatures, thereby improving the heat resistance of the pressure-sensitive adhesive. This is because the addition of hard monomers increases the rigidity of the molecular chain and reduces the mobility of the chain segments, so that the polymer requires a higher temperature to transform from the glassy state to the rubbery state. Monomers such as methacrylic acid, acrylic acid and internal crosslinking agents contain reactive functional groups, such as carboxyl, hydroxyl, and olefin groups. These functional groups can undergo crosslinking reactions with other acrylic components in the pressure-sensitive adhesive to form a three-dimensional network structure. This cross-linking effect can further improve the cohesion and temperature resistance of the pressure-sensitive adhesive, making it less likely to soften or lose viscosity at high temperatures. The addition of methacrylic acid and acrylic acid also increases the rigidity of the polymer molecular chain and reduces the free rotation of the chain segments, which helps to increase the Tg of the polymer, thereby improving the temperature resistance of the pressure-sensitive adhesive.

[0050] After adding a small amount of nano-ceramic particles during the polymerization reaction of the pressure-sensitive adhesive, the purpose is to evenly distribute the nano-ceramic particles in the pressure-sensitive adhesive body. A small amount of nano-ceramic particles has the following effects and mechanisms in the finished adhesive. When the proportion of nano-ceramic particles is appropriate, they can reach a stage of mutual contact and form a tighter filling structure, which helps to improve the mechanical properties of the pressure-sensitive adhesive and maintain better structural stability under high temperature or stress conditions. Nano-ceramic particles, especially those with hydrophilic properties, can also improve the hydrophilicity of the pressure-sensitive adhesive and increase its permeability. This not only helps the pressure-sensitive adhesive to better contact the substrate during application, but may also enhance its adhesion properties in humid environments.

[0051] The addition of nano-ceramic particles can also enhance the creep resistance of pressure-sensitive adhesives, that is, the ability to resist deformation under continuous stress. In addition, nano-ceramic particles usually have high thermal stability. Their addition can improve the thermal stability of pressure-sensitive adhesives, making them less likely to decompose or lose performance at high temperatures. Finally, the chemical stability of nano-ceramic particles is usually better than that of organic materials. Their addition can improve the resistance of pressure-sensitive adhesives to chemicals, thereby maintaining better performance in harsh environments. And the addition of nano-ceramic particles in the polymerization reaction can further stabilize the polymerization reaction rate, prevent violent boiling, and improve the production quality of pressure-sensitive adhesives.

[0052] Polyvinyl formal is applied on the surface of the aluminum foil tape to adhere nano-ceramic particles. A heat absorbing layer is constructed between the aluminum foil tape and the pressure-sensitive adhesive. After the heat is quickly transferred to the aluminum foil, the heat is quickly transferred to the air through the excellent thermal conductivity of the aluminum foil as a metal and the high heat exchange rate brought by the large area, thereby improving the temperature resistance of the aluminum foil tape.

[0053] The nano-ceramic particles are attached by using polyvinyl formal because polyvinyl formal has good temperature resistance (it only softens at 140-150°C), and contains a large number of hydroxyl groups in its structure, which can produce hydrogen bond structures and strong van der Waals forces with polyacrylic acid monomers, while ensuring the temperature resistance of the aluminum foil tape, and further improving the adhesion between the pressure-sensitive adhesive and the nano-ceramic particles. Furthermore, heating polyvinyl formal to 50-170°C can promote the cross-linking reaction, especially at 150 degrees Celsius, it can melt at the interface with acrylic compositions. Polyvinyl formal has a certain compatibility with acrylic substances at the molecular level, and a more stable composite system can be formed through interfacial melting. This enhanced compatibility helps to improve the mechanical properties and thermal stability of the composite material.

[0054] The non-hydrophilic nano ceramic particles used in the present invention include silicon nitride (Si 3 N 4 ) and silicon carbide (SiC), hydrophilic nano-ceramic particles include alumina (Al 2 O 3 ) and zirconium oxide (ZrO 2 ), polyvinyl formal contains a large number of hydroxyl groups and exhibits a strong polarity. Aluminum oxide and / or zirconium oxide materials form a mixed layer with polyvinyl formal, which can produce better bonding properties with polyvinyl formal than silicon carbide and / or silicon nitride due to the difference in polarity, specifically including van der Waals force and hydrogen bonding. The hydrogen bonding effect of silicon nitride is second, but the above materials show good effects in the process of improving the pressure-sensitive adhesive-aluminum foil tape.

[0055] According to the flat wall heat conduction formula, Q = λF(ΔT) / δ. Where: Q is the amount of heat transferred through the flat wall, W, directly measured using a heat flow meter; λ is the thermal conductivity of the flat wall material, W / (m*℃); F is the flat wall area, ㎡, directly measured using a ruler; ΔT is the temperature difference between the two sides of the flat wall, ℃. During the experiment, the temperature of the heated wall on the side of the pressure-sensitive adhesive is known, and the temperature on the side of the aluminum foil tape is measured using a thermocouple / thermometer; δ is the thickness of the flat wall, m. In each embodiment, the thickness of the aluminum foil layer and the polyvinyl formal layer are approximately 14μm and 10μm, and the thickness of the pressure-sensitive adhesive is approximately 20μm. The calculated average thermal conductivity of the materials in each embodiment is 58W / (m*℃).

[0056] It should be noted that the thickness of the polyvinyl formal layer is 8 to 12 μm. If it is too thin, the heat transfer effect will be reduced, while if it is too thick, it will affect the deflection of the aluminum foil tape and thus affect its use.

[0057] Snowtack 881G tackifying emulsion was purchased from Shanghai Sangjing Chemical Co., Ltd. Its physicochemical parameters are as follows: solid content 55%, viscosity 300mPa*s, pH=9, residue <100ppm, average particle size 0.6μm, density 1.02g / mL, softening point 96℃, acid value <20mg / KOH, glass transition temperature 45℃. It is a water-based rosin tackifying emulsion.

[0058] JZ-290 thickener was purchased from Shanghai Xianglan Chemical Co., Ltd. Its physical and chemical parameters are as follows: solid content 29-31%, density 1.05 g / mL, viscosity 0-50 cP, pH = 2.0-3.5. It is an anionic thickener.

[0059] The specific implementation of the present invention is further described below in conjunction with the examples. The following examples are only used to more clearly illustrate the technical solutions of the present invention, and cannot be used to limit the protection scope of the present invention.

[0060]

[0061]

[0062]

[0063]

[0064]

[0065]

[0066]

[0067]

[0068]

[0069]

[0070] The peel strength of the embodiment is measured by GB / 2792-2014 "Test method for peel strength of adhesive tape" as shown in the following table:

[0071] The adhesive strength of the embodiment is measured by GB / T4851-2014 "Test method for adhesive tape adhesiveness" as shown in the following table:

[0072] The initial adhesion performance of the embodiment is measured by GB / T4852-2014 "Pressure-sensitive Adhesive Tape Initial Adhesion Test Method" as shown in the following table:

[0073] The temperature resistance range of the embodiment is measured by GB / T32368-2015 "Test method for high temperature and high humidity aging of adhesive tape" as shown in the following table:

[0074] Peel strength Holding strength Initial adhesion performance Temperature range Embodiment 1 ≥12N / 25mm ≥28 hours ≤10cm -40℃~150℃ Embodiment 2 ≥14N / 25mm ≥31 hours ≤10cm -40℃~165℃ Embodiment 3 ≥14N / 25mm ≥30 hours ≤9cm -40℃~155℃ Embodiment 4 ≥15N / 25mm ≥ 29 hours ≤9cm -40℃~165℃ Embodiment 5 ≥13N / 25mm ≥40 hours ≤8cm -40℃~160℃ Embodiment 6 ≥13N / 25mm ≥42 hours ≤9cm -40℃~155℃ Embodiment 7 ≥15N / 25mm ≥48 hours ≤7cm -40℃~165℃ Embodiment 8 ≥15N / 25mm ≥48 hours ≤6cm -40℃~160℃ Embodiment 9 ≥16N / 25mm ≥48 hours ≤7cm -40℃~165℃

[0075] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A high temperature resistant emulsion type pressure sensitive adhesive, prepared by pre-emulsification and polymerization of raw rubber, characterized in that: The original rubber composition includes, by weight, 5-8 parts of reactive emulsifier, 300-365 parts of monomer, 200-300 parts of deionized water, 0-5 parts of internal crosslinking agent, 0.2-1 parts of surfactant, 1-5 parts of alkaline buffer, 1-5 parts of initiator; The monomer comprises the following components: 85-105 parts of isooctyl acrylate, 190-220 parts of n-butyl acrylate, 20-30 parts of vinyl acetate, and 5-10 parts of methacrylic acid and / or acrylic acid; the preparation method comprises: Pre-emulsification: S001: Mix the weighed reactive emulsifier in 100-150 parts of deionized water, which is called solution A; mix the monomer, internal crosslinking agent and surfactant, which is called solution B; S002: Add solution B dropwise into solution A, and the addition time is controlled to be completed within 1.5 to 2.5 hours; S003: Continue stirring the solution after the monomer has been added for 0.5 to 1.5 hours; The pre-emulsification is completed, and the mixed solution that has completed the pre-emulsification step is called solution C; Polymerization reaction: S101: adding solution C, alkaline buffer, initiator, remaining deionized water and 1 to 5 parts by weight of nano-ceramic particles into a reactor, turning on the stirring device of the reactor to stir evenly, heating the reactor to 75 to 85° C., and then dripping solution C into the reactor, with the dripping time controlled to be completed within 4 to 6 hours; S102: After the dropwise addition is completed, the temperature of the reactor is raised to 90-95° C. and maintained for 2-3 hours; S103: Turn off the heating device of the reactor, wait for the reactor to cool down to below 40° C., and take out the product; The polymerization reaction is completed, and the product that has completed the polymerization reaction step is called latex raw rubber; Synthesis of pressure sensitive adhesive: S201: 95-105 parts of the original latex, 20-30 parts of the thickening latex, 0.1-0.5 parts of the thickener, 0.5-1 parts of ammonia water, and 0.1-0.5 parts of the curing agent are added to a rubber mixing kettle, and stirred evenly in the rubber mixing kettle; S202: Using a viscosity meter to measure the viscosity of the contents in the adhesive preparation kettle, when it is between 2000 and 3500 centipoise and the solid content is between 54 and 56%, it is a pressure-sensitive adhesive.

2. The high temperature resistant emulsion pressure sensitive adhesive according to claim 1, characterized in that: Reactive emulsifiers include allyl ether sulfonates and / or acrylamide sulfonates; The internal crosslinking agent includes N-hydroxymethylacrylamide and / or N,N'-methylenebisacrylamide; The surfactant includes at least one of n-dodecyl mercaptan, n-hexadecyl mercaptan, sodium dodecyl sulfate, and sodium dodecylbenzene sulfonate; Alkaline buffers include sodium bicarbonate and / or potassium dihydrogen phosphate; The initiator includes at least one of ammonium persulfate, benzoyl peroxide and azobisisobutyronitrile.

3. The high temperature resistant emulsion pressure sensitive adhesive according to claim 1, characterized in that: The tackifying emulsion includes at least one of rosin tackifying emulsion, acrylate emulsion, styrene-butadiene emulsion, ethylene-vinyl acetate copolymer emulsion and silicone emulsion.

4. The high temperature resistant emulsion pressure sensitive adhesive according to any one of claims 1 to 3, characterized in that: The nano ceramic particles include SiC, Si3N 4、 At least one of Al2O3 and ZrO.

5. An aluminum foil tape made of the high temperature resistant emulsion pressure sensitive adhesive as claimed in any one of claims 1 to 4, characterized in that: The preparation method comprises: S301: coating the pressure-sensitive adhesive on the aluminum foil through a coating machine, drying it in an oven at 110° C. to 120° C. for 2 to 4 hours to remove volatiles, and stopping drying when the solid content reaches more than 85%; S302: Compounding the pressure-sensitive adhesive from which volatiles have been removed with a single-sided release paper to form a mother roll tape; S303: Cutting the mother roll tape into small rolls of tapes of various specifications, thus completing the production of the aluminum foil tape.

6. The aluminum foil tape according to claim 5, characterized in that: Before coating the aluminum foil in S301, the surface of the aluminum foil to be coated is first coated with nano ceramic particles with a thickness of 5 to 10 μm by brushing with adhesive.

7. The aluminum foil tape according to any one of claims 5 to 6, characterized in that: The nano ceramic particles include SiC, Si3N 4、 At least one of Al2O3 and ZrO.

8. The aluminum foil tape according to claim 6, characterized in that: The adhesive is newly made polyvinyl formal.

9. The aluminum foil tape according to any one of claims 6 to 8, characterized in that: The mixing ratio of the nano-ceramic particles to the adhesive is 0.5-0.7 g / mL.

10. The aluminum foil tape according to claim 9, characterized in that: The particle size of the nano-ceramic particles is 50 to 150 nm, and the thickness of the adhesive is 8 to 12 μm.

Citation Information

Patent Citations

  • Preparation methods of high-temperature-resistant adhesive and high-temperature-resistant aluminum tape

    CN109679540A

  • Emulsion of multi-component water-resistant adhesive tape as well as preparation process and application of emulsion

    CN117720681A